Illegal economic phenomena in the Russian agricultural sector - Yarkova, Tatyana M. (Revista de la Universidad del Zulia, 2020)
The current unstable market situation in Russia forces undesirable measures to be taken, mainly in the field of tax legislation for economic entities in the agricultural sector. This becomes a prior factor for the development of economic crime and the development of illegal phenomena. In recent years, there has been an increase in these crimes in the country. The agricultural sector of the Russian economy, as well as other countries, requires the availability of state financial support. However, during almost the entire post-Soviet period, a partial theft of state funds allocated to support and develop agricultural sectors can be observed under free market conditions. Such a problem exists everywhere in Russia. Existing methods of supervision and control over the use of budget allocations do not give the expected effect. In the context of such a negative situation, there is a need to develop effective methodological tools to assess the effectiveness and integrity of the use of budget funds for the agricultural sector, the algorithm of which is quite accessible and involves the use of scientific and practical methods, experience and knowledge of experts in the field of agriculture. This article aims to identify patterns of economic crime in agricultural and livestock production, and to propose methods for the evaluation and monitoring of public funds to Russian agricultural entities.